Polarization-Entangled Two-Photon Absorption in Inhomogeneously Broadened Ensembles - Schlawin, Frank (Frontiers in Physics, 2022)
Entangled photons are promising candidates for a variety of novel spectroscopic applications. In this paper, we simulate two-photon absorption (TPA) of entangled photons in a molecular ensemble with inhomogeneous broadening. We compare our results with a homogeneously broadened case and comment on the consequences for the possible quantum enhancement of TPA cross sections. We further consider the impact of the polarization degrees of freedom and carry out the orientational average of a model system Hamiltonian. We find that certain molecular geometries can give rise to a substantial polarization dependence of the entangled TPA rate.